Death in documentaries : the Memento Mori experience - Bennett-Carpenter, Benjamin (Value inquiry book series. Philosophy of film., 2018)
Memento mori is a broad and understudied cultural phenomenon and experience. The term "memento mori" is a Latin injunction that means "remember mortality," or more directly, "remember that you must die." In art and cultural history, memento mori appears widely, especially in medieval folk culture and in the well-known Dutch still life vanitas paintings of the sixteenth and seventeenth centuries. Yet memento mori extends well beyond these points in art and cultural history. In Death in Documentaries: The Memento Mori Experience, Benjamin Bennett-Carpenter suggests that documentaries are an especially apt form of contemporary memento mori . Bennett-Carpenter shows that documentaries may offer composed transformative experiences in which a viewer may renew one's consciousness of mortality - and thus renew one's life